A propensity score matching study: The prevalence of mental health problems among pregnant women at first antenatal care increased in Chongqing during the first wave of the COVID-19 pandemic - Guo, Jiamei; Li, Xiao; He, Jinglan; Ai, Ming; Gan, Yao; Zhang, Qi; Zheng, Anhai; Chen, Wanjun; Chen, Lulu; Liang, Sisi; Yu, Xiaoyu; Kuang, Li (Frontiers in Public Health, 2023)
Abstract Background: 2019 coronavirus disease (COVID-19) pandemic increased the risk of mental health problems, especially anxiety and depression. However, inconsistent results were reported on the impact of pregnancy on these problems during the pandemic. This study aimed to explore the impact of COVID-19 pandemic on the maternal mental health in a real world. Methods: Two cohorts of all pregnant women at their first antenatal care in our hospital were evaluated. One was enrolled before the COVID-19 outbreak (n = 5728, pre-COVID-19 group), and the other was enrolled during the COVID-19 pandemic (n = 739, COVID-19 pandemic group). The symptoms of depression, anxiety, and somatization were assessed by the PHQ-9, GAD-7, and PHQ-15, with a cut-off point of 10 for depression, GAD, and somatoform disorder, respectively. The propensity scores matching method (1:1) was applied to balance the differences in the demographic characteristics between the two groups. The chi-square analysis was used to compare the difference in the demographic characteristics between the two groups pre-and post- matched. Results: The prevalence of depression, GAD, and somatoform disorder among pregnant women at their first antenatal care visit during COVID-19 pandemic (9.5%, 2.2%, 20.8%) was significantly lower than that before the pandemic (16.3%, 4.4% and 25.7%). Meanwhile, the number of women newly registered for antenatal care decreased by nearly 50% compared with the same period before the pandemic. There were significant differences in the distribution of demographic characteristics between the two groups (P＜ 0.05). And, after matching the demographic characteristics, the difference in the prevalence of maternal mental health between the two groups reversed dramatically. The prevalence of depression, GAD, and somatoform disorder in this population during the COVID-19 pandemic (2.3%, 9.6%, 20.8%) was significantly higher that before the pandemic (0.3%, 3.9%, and 10%). Conclusions: COVID-19 pandemic would increase the risk for the mental health problems among pregnant women. Unfortunately, a great proportion of pregnant women with these problems may not attend the clinic for antenatal care as expected, which might lead to the fake phenomenon of a significant lower incidence of mental health problems in the clinic.